If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 7 = 8 Reorder the terms: 7 + 5x = 8 Solving 7 + 5x = 8 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 5x = 8 + -7 Combine like terms: 7 + -7 = 0 0 + 5x = 8 + -7 5x = 8 + -7 Combine like terms: 8 + -7 = 1 5x = 1 Divide each side by '5'. x = 0.2 Simplifying x = 0.2
| 15w-2(w+5)=11 | | 4xp=68 | | 9x+3=7x+45 | | 7X-3=4x+10+2 | | (x+5-3i)(x+5+3i)(x-2)(x-2)= | | 3/8r=-24 | | 4p-3=25 | | 5+3(5x-1)=32 | | 2+5+6x=x+42 | | x+3/5-7=-2 | | 3/8r=24 | | 2n+14=30 | | x^4/(2-x)^4=0 | | 2x+3x+9=90 | | x^4/(2-x)^4 | | 4d-8=4 | | 25+10x=44+21x | | 5*x-7=8 | | 7xy-7y^2-12x=0 | | 6-4x=50 | | x^3+12x^2+9x+27=0 | | 9x/5=-36 | | 2b-10b+b= | | (ab-2a)x=3b-6 | | 8(6-2y)+41=9 | | 7+9x=2x-24 | | (2/3x-1/2)(3x/5-3/4)(4x-1/2)=0 | | 48=3(2x+2) | | x+24-2x=90 | | 13/22-11/26 | | x/3=11.2 | | 6t+3whent=-5 |